Mechanisms of DNA uptake by mammalian cells: fate of exogenously added DNA monitored by the use of fluorescent dyes. - Loyter, A (1982)
Coprecipitation of DNA with calcium phosphate is a commonly used method of gene transfer in mammalian cells. We have found that DNA forms a tight complex with Ca Pi and that DNA in this complex is resistant to nucleases present in serum or added externally. Under optimal conditions, virtually all of the recipient mouse Ltk- Aprt- cells take up Ca Pi--DNA complexes, as determined by fluorescent dyes specific for DNA (4',6-diaminilo-2-phenylindol dihydrochloride) or for calcium salts (chlorotetracycline). However, only a small proportion of the cells have detectable CA Pi--DNA complexes in the nucleus. Uptake of the Ca Pi--DNA complexes was highly dependent upon the pH at which the Ca Pi--DNA complexes was formed and upon the concentration of DNA in the complex.